(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive exploration of pronouns, focusing on their structural and semantic types as well as the theory of their grammatical categories. It categorizes pronouns into structural groups such as personal, possessive, reflexive, relative, demonstrative, indefinite, and interrogative, explaining the distinct functions each type performs in language. The article also delves into the semantic roles of pronouns, including anaphoric, cataphoric, deictic, and exophoric uses, illustrating how pronouns link ideas across sentences and rely on context for meaning. Additionally, it covers the grammatical categories of pronouns, including person, number, gender, case, formality, inclusivity, and reciprocity, highlighting their role in shaping sentence structure and communication. This article serves as an essential resource for understanding the multifaceted nature of pronouns and their central importance in language.